Oral health status of patients on hemodialysis in Zliten-Libya - Algdar, Muftah A ASwisi (My University, 2016)
Introduction Chronic Kidney Disease (CKD) is an emerging health problem worldwide. Furthermore, 90% of CKD patients have been shown to have oral manifestations related to the disease. The prevalence of CKD in Libya is 624 per million population. There is a lack of literature on the oral health status of CKD patients in Libya, and oral health practitioners are increasingly likely to encounter these patients. Aims and objectives The purpose of this study was to assess the dental and periodontal health of CKD patients on hemodialysis at the Zliten dialysis centre in Libya. The objectives were to determine the prevalence of dental caries, the periodontal status and the treatment needs of the patients, and to compare the effect of hemodialysis duration on oral health status. Methodology Data was collected by means of a structured interview questionnaire focusing on demographic information, medical history and dental information of an adult cohort. This was followed by an oral examination using two indices: Decayed Missing Filled Teeth (DMFT) and the Community Periodontal Index of Treatment Need (CPITN). Results Seventy-two (N=72) adults consented to participate in the study. The prevalence of dental caries was 86%, and the mean DMFT was 5.96 (SD 5.41). The CPITN results showed that the majority of the participants (44.4%) had scored 3, indicating the presence of 4-5mm shallow pockets. There was no significant effect of hemodialysis duration on the DMFT (p=0.5) or the CPITN (p=0.8). Conclusion Though the oral health status of the patients was poor, the effect of duration of hemodialysis on the dental and periodontal status was not significant.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Dentistry. School of Oral Health Sciences, Faculty of Health Sciences University of the Witwatersrand, South Africa Johannesburg, 2016